The Effect of TEACCH Method towards Self-Help Ability on Wearing Clothes for Children with Down Syndrome - Ismanura Firdaus; Ahmad Samawi (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
Children with Down syndrome have intellectual delay in their coginitive development. One of the characteristics is the low ability of self-development. The aim of this research is to describe the effect of the TEACCH method towards the ability of self-help on wearing clothes for down syndrome students. The research was arranged based on the Single Subject Research (SSR) experimental method with the A-B-A design. The conclusion of this research is that the intervention using the TEACCH method can establish the ability to wear clothes of Down syndrome students.